Facile synthesis of micrometer-long antimony nanowires by template-free electrodeposition for next generation Li-ion batteries. Issue 33 (4th August 2016) - Al-Salman, R.; Sedlmaier, S. J.; Sommer, H.; Brezesinski, T.; Janek, J.
Abstract : High quality Sb nanowires of diameter < 50 nm can be electrodeposited from ionic liquid electrolytes containing GaCl3 and show promising Li-storage characteristics. Abstract : Template-free electrodeposition of high-aspect-ratio antimony nanowires at room temperature is reported. The nanowires with diameters down to 30 nm and lengths of up to several tens of micrometers are of high quality and grow very densely on different substrates such as copper and glassy carbon. Furthermore, they can be applied as a high capacity anode material in rechargeable Li-ion batteries with good capacity retention.